Biological degradation of potato pulp waste and microbial community structure in microbial fuel cells. Issue 14 (24th January 2017) - Tian, Yushi; Mei, Xiaoxue; Liang, Qing; Wu, Di; Ren, Nanqi; Xing, Defeng
Abstract : The syntrophic interactions between polysaccharide-degrading bacteria and exoelectrogens drove simultaneous alternative energy production and degradation of potato pulp waste in microbial fuel cells. Abstract : The microbial electrochemical cell (MEC) is a promising waste treatment technology to accomplish simultaneous alternative energy production and degradation of organic matters. Potato pulp waste (PPW) from a potato processing plant contains a large amount of carbohydrates that need be degradated before discharge into the environment. Here, we describe electricity generation in single-chamber microbial fuel cells (MFCs) using PPW. Different organic loadings of PPW influenced obviously the power output of MFCs. The maximum power density of 32.1 ± 0.5 W m −3 was obtained in a MFC fed with 10 g L −1 PPW. Microbial community analysis based on high-throughput sequencing of 16S rRNA gene indicated that the predominant populations were obviously different in the MFCs. The syntrophic interactions between polysaccharide-degrading bacteria and exoelectrogens in the anode biofilms drove the cascade utilization of potato pulp waste in MFCs.